Recognizing diversity to enable an agroecological transition: understanding the potential of family farmers in Portugal - Inês Costa-Pereira; Ana A. R. M. Aguiar; Fernanda Delgado; Cristina A. Costa (Frontiers in Sustainable Food Systems, 2025)
The agroecological transition of family farms in Portugal poses a significant challenge within the framework of the Common Agricultural Policy (CAP) and the European Green Deal. Despite their multifunctional contributions to rural territories, family farms—particularly smallholders—remain structurally disadvantaged by policy frameworks that continue to favor large-scale, high-input agricultural models. This study demonstrates that aligning family farming with agroecological principles yields tangible benefits and requires support through differentiated, typology-sensitive public policies. Using a tailored methodology, data were collected from 40 farms initially classified as conventional or agroecological. Ward’s hierarchical clustering, supported by complementary significance tests, identified three distinct farmer typologies: conventional, proto-agroecological, and agroecological. These typologies reflect meaningful differences in ecological integration, systemic thinking, and social engagement. The findings highlight the need for targeted policy frameworks that recognize farm diversity and promote multiple pathways toward agroecology. This typology-based approach provides an empirically grounded foundation for designing more inclusive and context-responsive institutional support for family farmers in Portugal.